Speed, power and area optimized monotonic asynchronous array multipliers - Balasubramanian, Padmanabhan (2024)
Multiplication is a fundamental arithmetic operation in electronic processing units such as microprocessors and digital signal processors as it plays an important role in various computational tasks and applications. There exist many designs of synchronous multipliers in the literature. However, in the domain of Input–Output Mode (IOM) asynchronous design, there is relatively less published research on multipliers. Some existing works have considered quasi-delay-insensitive (QDI) asynchronous implementations of multipliers. However, the QDI asynchronous design paradigm, in general, is not area- and speed-efficient. This article presents an efficient alternative implementation of IOM asynchronous multipliers based on the concept of monotonic Boolean networks. The array multiplier architecture has been considered for demonstrating the usefulness of our proposition. The building blocks of the multiplier, such as the partial product generator, half adder, and full adder, were implemented monotonically. The popular dual-rail encoding scheme was considered for encoding the multiplier inputs and outputs, and four-phase return-to-zero handshaking (RZH) and return-to-one handshaking (ROH) were separately considered for communication. Compared to the best of the existing QDI asynchronous array multipliers, the proposed monotonic asynchronous array multiplier achieves the following reductions in design metrics: (i) a 40.1% (44.3%) reduction in cycle time (which is the asynchronous equivalent of synchronous clock timing), a 37.7% (37.7%) reduction in area, and a 4% (4.5%) reduction in power for 4 × 4 multiplication corresponding to RZH (ROH), and (ii) a 58.1% (60.2%) reduction in cycle time, a 45.2% (45.2%) reduction in area, and a 10.3% (11%) reduction in power for 8 × 8 multiplication corresponding to RZH (ROH). The multipliers were implemented using a 28 nm CMOS process technology.